Frequency of Raised Intracranial Pressure in Patients with Brain Tumours; Primary or Secondary to Another Primary Tumour - Jafar, Amina; Iqbal, Rabia; Bajwa, Ahmad Taimoor; Raza, Aun (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of raised intracranial pressure in patients with brain tumours.” Study-Design: Cross-Sectional Study design. Place & duration of study: “Department of Medicine, Shaukat Khanum Memorial Cancer Hospital, Lahore,” from February, 2024 till October, 2024. Subjects and method: 100 patients with brain tumours were enrolled and intracranial pressure was examined. Data was noted in proforma, while entered and analysed in “Statistical Package for Social Sciences (SPSS)” version 20. Outcome: Among 100 patients of brain tumors, raised intracranial pressure was observed in 33 (33%) patients. It has been observed that raised ICP was significantly higher in patients above 55 years old (68.4%) as compared to younger age groups (p<0.05). Conclusion: This study demonstrated that a significant proportion of patients (33% in our cohort) with brain tumors, regardless of whether they are primary or secondary, exhibit raised ICP, highlighting the importance of monitoring and managing ICP in this patient population at an early stage. It would help to prevent further neurological deterioration and use of unnecessary testing in these patients.